2020
DOI: 10.1002/cbf.3590
|View full text |Cite
|
Sign up to set email alerts
|

Context is key: Understanding the regulation, functional control, and activities of the p53 tumour suppressor

Abstract: The p53 tumour suppressor is considered one of the most critical genes in cancer biology. By upregulating apoptosis, cell cycle arrest, and DNA damage repair in normal cells, p53 prevents the propagation of cells with tumorigenic potential; therefore, mutations in p53 are associated with carcinogenic transformation and can be accompanied by the accumulation of a novel gain‐of‐function oncogenic protein, mutant p53. Although p53 is most often understood to utilize context‐dependent post‐translational modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 173 publications
(255 reference statements)
0
15
0
Order By: Relevance
“…MDA-MB-231 cells bear the R280K mutation in the p53 DNA-binding domain, which renders p53 defective in transcription activation [ 74 , 75 ], leading to an impairment in G1 arrest [ 76 , 77 ]. The impact of p53 activity on the efficacy of RAD51i is of significant interest, because approximately 50% of all cancers carry p53 mutations [ 78 ]. Recently, it was shown that p53 may either promote or antagonize the anti-proliferating effect of B02 alone or in combination with topotecan in retinoblastoma cells depending on whether the BAX (apoptotic) or p21 (G1 cell cycle arrest) pathways predominate in these cells [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB-231 cells bear the R280K mutation in the p53 DNA-binding domain, which renders p53 defective in transcription activation [ 74 , 75 ], leading to an impairment in G1 arrest [ 76 , 77 ]. The impact of p53 activity on the efficacy of RAD51i is of significant interest, because approximately 50% of all cancers carry p53 mutations [ 78 ]. Recently, it was shown that p53 may either promote or antagonize the anti-proliferating effect of B02 alone or in combination with topotecan in retinoblastoma cells depending on whether the BAX (apoptotic) or p21 (G1 cell cycle arrest) pathways predominate in these cells [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations of the current study. As is well known, p53 protein has a very complex network of activity [ 50 ]. In the study, we did not provide a mechanistic interpretation of how p53, MDM2, and miR-29a interact, especially regarding the crosstalk between the status of p53 (wild-type vs mutated) and miR-29a.…”
Section: Discussionmentioning
confidence: 99%
“…It is a sequence-specific transcription factor that is a critical regulator of tumor suppression caused due to genomic instability. [41] Under normal conditions, p53 levels are maintained low, and its expression is induced upon DNA damage F I G U R E 1 Regulation of p53 mRNA translation and stability upon genotoxic stress. In addition to regulation of p53 protein level by p53-MDM2 axis, multiple proteins such as NCL, PTB, MDM2, and RPL26 regulate p53 protein levels by affecting mRNA translation and/or stability.…”
Section: P53 Mrna Regulation Is Mediated By Multiple Rbpsmentioning
confidence: 99%